2011
DOI: 10.1103/physrevb.84.233201
|View full text |Cite
|
Sign up to set email alerts
|

Reassignment of the OTe-VCdcomplex in CdTe

Abstract: An IR absorption study of single-crystal CdTe annealed in CdSO 4 vapor at 850 • C is presented. It is shown that such a treatment results in the appearance of two absorption lines ν 1 and ν 2 at 1096.8 and 1108.4 cm −1 , respectively [G. Chen et al., Phys. Rev. Lett. 96, 035508 (2006); Phys. Rev. B 75, 125204 (2007)]. Each of these features is accompanied by weaker lines. The intensities of each set of lines match the natural abundance of the sulfur isotopes. The ν 1 and ν 2 modes are assigned to the stretch v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…In this paper, we focused our attentions on the study of oxygen O and sulfur S complex defects in CdTe based on the experimental results studied by Lavrov et al 10 and Chen et al 6 There are several plausible candidates of oxygensulfur complex defects in CdTe to be investigated. To gain a better understanding of the building block of these complexes, first, individual defects (O and S) were separately investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we focused our attentions on the study of oxygen O and sulfur S complex defects in CdTe based on the experimental results studied by Lavrov et al 10 and Chen et al 6 There are several plausible candidates of oxygensulfur complex defects in CdTe to be investigated. To gain a better understanding of the building block of these complexes, first, individual defects (O and S) were separately investigated.…”
Section: Resultsmentioning
confidence: 99%
“…8 More recently, Lavrov et al have experimentally reexamined the LVMs of oxygen impurity in CdTe by using FTIR technique. 10 In their work, the sample was prepared by using single-crystal CdTe and CdSO 4 vapor as a source of sulfur and oxygen impurities. Surprisingly, the IR absorption lines at 1096.8 and 1108.4 cm À1 were reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation could be a formation of other sulfur-oxygen-related complexes with LVMs close to the γ-lines. Based on the similarities between CdSe and the results obtained for the SO * 2 complex in CdTe we suggest that the γ-lines have the same origin [12]. Theoretical support of this model is needed.…”
Section: Resultsmentioning
confidence: 68%
“…It is shown that a sulfur-dioxygen (SO * 2 ) complex is the most plausible candidate for the γ-lines. Note that a similar situation was reported in CdTe where two absorption lines originally attributed to the LVMs of a O Te -V Cd complex [10,11] were recently reassigned to LVMs of different orientations of a SO * 2 in the host lattice [12].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation